Medical tourism based on natural ingredients and health structures as one of the solutions to obilize economic resources - Abdelkader, Slim Bourchid; Mousa, Elsiddig Yousif Mohammed (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed at analyzing and evaluating the incentive factors in the field of medical tourism, and encouraging investment in them in Algeria, in order to attract foreign tourists, enter foreign currency and get out of economic dependence, in addition to highlighting the potential of Algeria's tourism that allows it to establish a tourism activity based on health structures and medical centers. medical treatment, The researcher used the descriptive analytical approach to address the variables of the study. After the study and analysis, the researcher reached several results, the most important of which is the failure to make good use of the potential that Algeria harnesses in the field of medical tourism, and the weakness of the results achieved in the field compared to these capabilities. Based on the results achieved, the researcher presented a set of recommendations, the most important of which is the need to work on finding clear mechanisms that enable the good exploitation of natural resources and their good exploitation, and work on exploiting what is available in order to market these capabilities at the national and international levels.
Keywords: Tourism; medical tourism; water baths; Health structures